Conditional Deletion of Activating Rearranged During Transfection Receptor Tyrosine Kinase Leads to Impairment of Photoreceptor Ribbon Synapses and Disrupted Visual Function in Mice - Peng, Wei-Hao; Liao, Meng-Lin; Huang, Wan-Chun; Liu, Pei-Kang; Levi, Sarah R.; Tseng, Yun-Ju; Lee, Chia-Ying; Yeh, Lung-Kun; Chen, Kuan-Jen; Chien, Chung-Liang; Wang, Nan-Kai (Frontiers in Neuroscience, 2021)
Purpose The rearranged during transfection (RET) receptor tyrosine kinase plays a key role in transducing signals related to cell growth and differentiation. Ret mutant mice show abnormal retinal activity and abnormal levels and morphology of bipolar cells, yet die on the 21st day after birth as a result of renal underdevelopment. To extend the observation period, we generated the Ret conditional knockout Chx10-Cre;C-Retlx/lx mouse model and analyzed the retinal function and morphological changes in mature and aging Chx10-Cre;C-Retlx/lx mice. Methods Retina-specific depletion of Ret was achieved using mice with floxed alleles of the Ret gene with CHX10-driven Cre recombinase; floxed mice without Cre expression were used as controls. Retinal function was examined using electroretinography (ERG), and 2-, 4-, 12-, and 24-month-old mice were analyzed by hematoxylin staining and immunohistochemistry to evaluate retinal morphological alterations. The ultrastructure of photoreceptor synapses was evaluated using electron microscopy. Results The results of the ERG testing showed that b-wave amplitudes were reduced in Chx10-Cre;C-Retlx/lx mice, whereas a-waves were not affected. A histopathological analysis revealed a thinner and disorganized outer plexiform layer at the ages of 12 and 24 months in Chx10-Cre;C-Retlx/lx mice. Moreover, the data provided by immunohistochemistry showed defects in the synapses of photoreceptor cells. This result was confirmed at the ultrastructural level, thus supporting the participation of Ret in the morphological changes of the synaptic ribbon. Conclusions Our results provide evidence of the role of Ret in maintaining the function of the retina, which was essential for preserving the structure of the synaptic ribbon and supporting the integrity of the outer plexiform layer.